Implementation of Multi-Attribute Utility Theory and Borda Count Method for Selecting Tahfidzul Qur'an Islamic Boarding Schools - Ilmiyah, Nur Fadilatul; Salsabela, Qothrun Nada; Rohmah, Nafilatur; Nisa, Afifatun (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
This descriptive qualitative research aims to provide an overview of the implementation of the Multy Attribute Utility Theory and Borda Count Methods in compiling recommendations for selecting Tahfidzul Qur'an Islamic boarding schools that align with the expectations of prospective students. This research consists of five stages: compiling criteria and their measurement scale, determining the preference weight of each criterion for each decision maker, implementing the MAUT Method, implementing the Borda Count Method, and compiling recommendations. The research results show that both methods can support selecting the best Tahfidz Islamic boarding school, according to what the students expect. From the calculation results, the Tahfidzul Qur'an boarding school with code PPTQ03 is the boarding school that best fits the preference weight of the decision-makers